P029: Paramedic and nurse-staffed rural collaborative emergency centres: the rate of relapse for discharged patients. (15th May 2017) - Carter, A.; Cook, J.; Beals, M.; Goldstein, J.; Travers, A.; Jensen, J.; Dobson, T.; Carrigan, S.A.; Vanberkel, P.
Abstract : Introduction: Collaborative Emergency Centres (CECs) provide access to care in rural communities. After hours, registered nurses (RNs) and paramedics work together in the ED with telephone support by an emergency medical services (EMS) physician. The safety of such a model is unknown. Relapse visits are often used as a proxy measure for safety in emergency medicine. The primary outcome of this study is to measure unscheduled relapses to emergency care.Methods: The electronic patient care record (ePCR) database was queried for all patients who visited two CECs from April 1, 2012 to April 1, 2013. Abstracted data included demographics, time, acuity score, clinical impression, chief complaint, and disposition. Records were searched for each discharged CEC patient to identify unscheduled relapses to emergency care, defined as presenting back to EMS, CEC, or any other ED within the Health Authority within 48 hours of CEC discharge.Results: There were 894 CEC visits, of which 66 were excluded due to missing data. The dispositions from CEC were: 131/828 (15.8%) transferred to regional ED; 264/828 (31.9%) discharged home; 488/828 (58.9%) discharged with follow up visit booked; and 11/82 (1.2%) left the CEC without being seen. There was 37/828 (4.5%) visits which relapsed back to emergency care, all of whom were discharged from CEC or left without being seen: 3/828 (0.4%) relapsed back to EMS (two taken to regional ED and one to CEC); 16/828 (1.9%) relapsed to regional ED (by walking-in); and 18/828 (2.2%) had a relapse to the CEC (walk-in). 516/828 (62.3%) CEC visits were resolved in a single visit.Conclusion: This study was based on only two of the 7 operating CECs due to accessing paper-based charts for multiple health regions. We also acknowledge the limitations of using relapse as a proxy for safety, and that low volumes and acuity will make detection of adverse events challenging. Albeit a proxy measure, the rate of patients who relapse to emergency care was under 5% in this case series of two CECs. Most patients had their concern resolved in a single visit to a CEC. Further research is underway to determine the effectiveness, optimal utilization and safety of this collaborative model of rural emergency care.